How Are We Going to Produce Our Future Resource Professionals? (The Australasian Institute of Mining and Metallurgy, 1997)
The closure of the only professional mining school in New Zealand will mean that the minerals industry will have to explore other options to fill their mining professional positions. Globally mining is not seen as an attractive career option for young people and recruitment into mining courses is at a low level. Yet industry demands ever increasing competencies with respect to technology, environmental issues and legislation. This paper addresses this issue by first discussing the attributes required of graduate mining professionals. It then looks at alternative ways on how these can be met internationally and on the home front.